Efektivitas Kelembagaan Pengembangan Ekowisata Dalam Mendukung Implementasi Kebijakan Hukum Terkait Ekowisata di Kota Baubau Sulawesi Tenggara - Nur Saadah (Lembaga Pengembangan Kinerja Dosen, 2024)
Ecotourism in Baubau City has not developed optimally despite having great natural resource potential. Weak coordination between institutions is one of the obstacles to the implementation of policies related to ecotourism development. The purpose of this study was to analyze the effectiveness of the role of ecotourism development institutions in supporting ecotourism policies in Baubau City. This research uses qualitative methods with data collection techniques of observation and in-depth interviews with related agencies and local ecotourism actors. The results showed that coordination between ecotourism development institutions is still weak so that the implementation of ecotourism policies is not optimal. Recommendations include the need to improve cross-sectoral coordination and program synchronization, optimize the function of ecotourism institutions, and increase human resource capacity. This research is useful as an evaluation for policy makers related to ecotourism institutional reform in Baubau City.